Closed loop force control of in-situ machining robots using audible sound features. (February 2020) - Alatorre, David; Rabani, Amir; Axinte, Dragos; Branson, David T.
Highlights: Airborne sound features can be used to control cutting forces while grinding. Dominant frequency can be used to monitor and control air spindle velocity. Sound intensity can be used to mitigate the effects of workpiece resonance. Proposed control method can achieve accuracy of 0.08 N with air-driven tools. Demonstrated with robotic arm grinding objects with unknown topology. Abstract: Detecting, measuring and controlling the forces between cutting tools and machined components is essential in circumstances where direct position control (e.g. depth of cut, feed speed, etc.) is inaccurate and/or impossible. This paper explores the use of airborne sound signals that result from the machining process to control the cutting force in closed loop for generating accurate machined features when performing in-situ robotic repair of complex installations. The sound signals during indentation at various cutting forces are analysed and used to calibrate a remotely mounted microphone sensor and signal processing control system. The power spectral density of the audible sound is used to estimate tool cutting force and the sound intensity used in turn to estimate the resulting process energy. The described controller uses intensity of sound to mitigate the effects of resonance with workpiece natural frequencies while controlling the spindle velocity of the tool based on the dominant audible frequency. The performance of the controller is validated using a representative test rig and demonstrated using a robotic arm to machine thin Ni-Cr-Co alloy cantilever beams with a miniature air-driven grinding tool. Results from the test rig show that such a sound-based control approach can achieve consistent cutting forces with an accuracy of 0.08 N. The robot arm is shown to be capable of grinding features of consistent depth (to within 0.05 mm) on beams with surface defects of undefined shape using only the sound of the process for closed loop force control.